Flexible and Stable GaN Piezoelectric Sensor for Motion Monitoring and Fall Warning - Zhiling Chen; Kun Lv; Renqiang Zhao; Yaxian Lu; Ping Chen (Nanomaterials)
Wearable devices have potential applications in health monitoring and personalized healthcare due to their portability, conformability, and excellent mechanical flexibility. However, their performance is often limited by instability in acidic or basic environments. In this study, a flexible sensor with excellent stability based on a GaN nanoplate was developed through a simple and controllable fabrication process, where the linearity and stability remained at almost 99% of the original performance for 40 days in an air atmosphere. Moreover, perfect stability was also demonstrated in acid–base environments, with pH values ranging from 1 to 13. Based on its excellent stability and piezotronic performance, a flexible device for motion monitoring was developed, capable of detecting motions such as finger, knee, and wrist bending, as well as swallowing. Furthermore, gesture recognition and intelligent fall monitoring were explored based on the bending properties. In addition, an intelligent fall warning system was proposed for the personalized healthcare application of elders by applying machine learning to analyze data collected from typical activities. Our research provides a path for stable and flexible electronics and personalized healthcare applications.